The Most Effective Strategies to Curb Corruption and Improve Water Service Delivery in Zimbabwe - Mutuma, Patrick; Jambawo, Trevor (Journal of Economics and Behavioral Studies, 2017)
The main objective of this study was to find the most effective strategies to curb and eradicate corruption and improve water service delivery. The study also aimed to present the type, causes, and effects of corruption. A mixed-methods questionnaire survey design was used to collect quantitative and qualitative data. 220 questionnaires were distributed to providers and users of water services in Zimbabwe. 149 respondents returned the completed questionnaires. Data were analysed using descriptive statistics and content analysis. The Analysis of Variance was used to test the significance of mean scores. The study revealed that corruption is highly prevalent in Zimbabwe. The main factors that cause corruption in the water sector are poor governance, economic hardship, and weak accountability. Corruption leads to economic stagnation and poor foreign investments. Organisations such as the Zimbabwe National Water Authority must improve systems and structures, enhance the auditing process, and educate staff on good ethical standards and effective governance to effectively fight against corruption and improve service delivery. They must also put in place strong governance and accountability frameworks and work closely with communities and policy makers to eradicate corruption. The availability of water should be the same across all the suburbs, and the country needs to adjust its water bill rates in line with regional rates. Service providers should make use of mobile technology to promote citizenry participation in sharing ideas and making decisions on water sustainability. This study reaffirms the need to fight corruption and improve water service delivery.